Reactive strength index and its associations with measures of physical and sports performance: a systematic review with meta-analysis - Jarvis, P.; Turner, A.; Read, P.; Bishop, C. (Sports Medicine, 2022)
Background: Reactive strength index (RSI) is used frequently in the testing and monitoring of athletes. Associations with sports performance measures may vary dependent on the task but a literature synthesis has not been performed. Objectives: The aim of this meta-analysis was to examine associations between RSI measured during rebound jumping tasks and measures of strength, linear and change of direction speed, and endurance performance. Methods: A systematic literature search with meta-analysis was conducted using databases PubMed, SPORTDiscus, Web of Science, and Ovid. Inclusion criteria required studies to (1) examine the relationship between RSI and an independent measure of physical or sporting performance for at least one variable; and (2) provide rebound test instructions to minimise ground contact time and maximise displacement of the jump. Methodological quality was assessed using a modified version of the Downs and Black Quality Index tool. Heterogeneity was examined via the Q statistic and I2. Pooled effect sizes were calculated using a random-effects model, with Egger`s regression test used to assess small study bias (inclusive of publication bias). Results: Of the 1320 citations reviewed, a total of 32 studies were included in this meta-analysis. RSI was significantly and moderately associated with strength (isometric: r = 0.356 [95% CI 0.209-0.504]; isotonic: r = 0.365 [0.075-0.654]; pooled strength measures: r = 0.339 [0.209-0.469]) and endurance performance (r = 0.401 [0.173-0.629]). Significant moderate and negative associations were indicated for acceleration (r = - 0.426 [- 0.562 to - 0.290]), top speed (r = - 0.326 [- 0.502 to - 0.151]), and significant large negative associations were noted for change of direction speed (r = - 0.565 [- 0.726 to - 0.404]). Heterogeneity was trivial to moderate across all measures (I2 = 0-66%), and significant for isotonic strength and change of direction speed (p < 0.1). Evidence of small study bias was apparent for both acceleration and change of direction speed (p < 0.05). Conclusions: We identified primarily moderate associations between RSI and independent measures of physical and sporting performance, and the strength of these relationships varied based on the task and physical quality assessed. The findings from this meta-analysis can help practitioners to develop more targeted testing and monitoring processes. Future research may wish to examine if associations are stronger in tasks that display greater specificity.